Enhancing Virus Filter Performance Through Pretreatment by Membrane Adsorbers - Solomon Isu; Shu-Ting Chen; Raheleh Daneshpour; Hironobu Shirataki; Daniel Strauss; Andrew L. Zydney; Xianghong Qian; Sumith Ranil Wickramasinghe (Membranes)
Virus filtration is used to ensure the high level of virus clearance required in the manufacture of biopharmaceutical products such as monoclonal antibodies. Flux decline during virus filtration can occur due to the formation of reversible aggregates consisting of self-assembled monomeric monoclonal antibody molecules, particularly at high antibody concentrations. While size exclusion chromatography is generally unable to detect these reversible aggregates, dynamic light scattering may be used to determine their presence. Flux decline during virus filtration may be minimized by pretreating the feed using a membrane adsorber in order to disrupt the reversible aggregates that are present. The formation of reversible aggregates is highly dependent on the monoclonal antibody and the feed conditions. For the pH values investigated here, pretreatment of the feed using a hydrophobic interaction membrane adsorber was the most effective in minimizing flux decline during virus filtration. Ion exchange membranes may also be effective if the monoclonal antibody and membrane are oppositely charged. Consequently, the effectiveness of ion exchange membrane adsorbers is much more dependent on solution pH when compared to hydrophobic interaction membrane adsorbers. Size based prefiltration was found to be ineffective at disrupting these reversible aggregates. These results can help guide the development of more effective virus filtration processes for monoclonal antibody production.